2020
DOI: 10.1002/cam4.2876
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the relevance of circulating tumor cell status and neoadjuvant chemotherapy effectiveness in early breast cancer

Abstract: Although unequivocal evidence has shown the prognostic relevance of circulating tumor cells (CTCs) in patients with metastatic breast cancer (MBC), less evidence is available for its significance in neoadjuvant chemotherapy (NCT) in early breast cancer (BC). Here we conducted an analysis of individual data from 86 patients confirmed as invasive BC by core‐needle biopsy in Zhejiang Provincial People's Hospital between June 2013 and January 2017. The CTCs were assessed at the time after diagnosis and before surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…The changing profile of metastatic potential (CTCs) and host immunity (CAMLs) over the course of treatment might be valuable for predicting pCR in the NAC setting using routine blood draws. Few studies have been done to correlate CTCs with OS and DFS in breast cancer patients undergoing NAC [ 43 , 44 , 45 , 46 , 47 ]. One study isolated E + CTCs before and after NAC and found that triple-negative and HER2-positive cancers were associated with worse OS and DFS if they had ≥2 CTCs/7.5 mL of blood before NAC [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The changing profile of metastatic potential (CTCs) and host immunity (CAMLs) over the course of treatment might be valuable for predicting pCR in the NAC setting using routine blood draws. Few studies have been done to correlate CTCs with OS and DFS in breast cancer patients undergoing NAC [ 43 , 44 , 45 , 46 , 47 ]. One study isolated E + CTCs before and after NAC and found that triple-negative and HER2-positive cancers were associated with worse OS and DFS if they had ≥2 CTCs/7.5 mL of blood before NAC [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, no association between CTC detection prior to neoadjuvant therapy and pathological response in early breast cancer has been shown (23,29). Recent evidence suggests conversion from CTC positive to CTC negative state after neoadjuvant therapy may be associated with some degree of pathological response (64). As this was a preliminary study in a small patient cohort, no extended protocol was in place to investigate prognostic relevance or monitor CTC dynamics longitudinally to make our data comparable to published literature.…”
Section: Discussionmentioning
confidence: 69%
“…Our study found no clinicopathological correlations with the presence of canonical or non-canonical CTCs before neoadjuvant setting, and no impact of detected CTCs on pCR. Published literature has shown correlations with tumor size ( 23 , 64 ), tumor stage, and molecular classification ( 64 ). Until recently, no association between CTC detection prior to neoadjuvant therapy and pathological response in early breast cancer has been shown ( 23 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study enrolled 86 early breast cancer patients and detected CTCs in 37.2% of cases, of which CTCs were correlated with tumor size, stage, molecular classification and preliminarily indicating the association of EMT CTCs and neoadjuvant chemotherapy effectiveness. 18 In a study with 651 localized colorectal cancer patients, CTCs were found in 535 patients, including 461 cases with the biophenotypic subtype, which associated with clinical stage. 19 The EMT CTC subtypes also correlated with disease progression and poor prognosis in early stage lung cancer and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%